Pengaruh Religiusitas, Pengetahuan Zakat dan Pendapatan Terhadap Kesadaran Berzakat Perkebunan Sawit - Firdaus Firdaus; Saifullah -; Sri Ika Mulia; Muhamad Muzamil (Indonesian Journal of Islamic Economics and Business, 2023)
This research is motivated by the large potential of oil palm plantations which is not in line with the community in paying zakat on oil palm plantations which is still low. The purpose of this study was to determine and analyze how the partial influence of religiosity, zakat knowledge and income on awareness of zakat on oil palm plantations in Bantan District. This research uses a quantitative approach with the help of SPSS 26.0. The results showed that partially religiosity and zakat knowledge had a positive and significant effect on zakat awareness of oil palm plantations in Bantan District while income had no effect on zakat awareness. This is due to the low income level of oil palm farmers. This is because most of the respondents' income cannot be categorized as large. This can be seen from the amount of palm oil productivity which is still low. Most oil palm farmers have land under 1 hectare and with a low level of productivity. So that the income they get is only able to meet the daily needs of their families.